Book Review: Fisher, W. F. (2001). Fluid Boundaries: Forming and Transforming Identity in Nepal. Columbia University Press. USA - Acharya, Pradeep (Dhaulagiri Journal of Sociology and Anthropology, 2012)
No abstract available. DOI: http://dx.doi.org/10.3126/dsaj.v5i0.6370 Dhaulagiri Journal of Sociology and Anthropology Vol. 5, 2011: 273-6